2013
DOI: 10.1111/cen.12338
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone replacement therapy in hypogonadal men is associated with increased expression of LAMP‐2 (CD107b) by circulating monocytes and dendritic cells

Abstract: These results support the existence of an effect of testosterone therapy, and potentially also of gonadotrophins, on circulating antigen-presenting cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…On the other hand, the circulating monocytes from hypogonadal men treated with testosterone replacement therapy exhibited significantly upregulated expression of CD107b at baseline compared to monocytes from healthy controls. This was also seen after stimulation with CpG oligodeoxynucleotides to mimic bacterial DNA exposure (280). Membrane expression of CD107b, also known as lysosome-associated membrane protein (LAMP)2, is indicative of release of lysosome and/or phagolysosome contents into the extracellular medium, a mechanism that may be involved in killing and/or digesting target cells.…”
Section: Testosterone Replacement In Menmentioning
confidence: 98%
“…On the other hand, the circulating monocytes from hypogonadal men treated with testosterone replacement therapy exhibited significantly upregulated expression of CD107b at baseline compared to monocytes from healthy controls. This was also seen after stimulation with CpG oligodeoxynucleotides to mimic bacterial DNA exposure (280). Membrane expression of CD107b, also known as lysosome-associated membrane protein (LAMP)2, is indicative of release of lysosome and/or phagolysosome contents into the extracellular medium, a mechanism that may be involved in killing and/or digesting target cells.…”
Section: Testosterone Replacement In Menmentioning
confidence: 98%
“…Although LAMP2 serum concentration was higher in healthy controls compared to CAD patients, we could not see significant difference between the 2 groups after a full adjustment. Several studies have reported altered expression of LAMP2 in PBMCs of different diseases [18][19][20], but to our knowledge there is only one study addressed LAMP2 serum level in a disease condition with which we compared our results of LAMP2 serum level. Our results are partly in consistent with this recently published study, which assessed LAMP2 serum concentrations in patients with primary biliary cirrhosis (PBC), viral hepatitis B (HBV), viral hepatitis C (HCV), intrahepatic cholestasis (IC) and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone treatment induced overexpression of LAMP-2 on both classical (CD16-) and nonclassical (CD16+) monocytes/DCs, a very high correlation being observed between LAMP-2 expression on these cells and both the LH and FSH serum levels [85]. Of note, overexpression of LAMP-2 was detected both ex vivo and after immunogenic stimulation in vitro [85]. As LAMP-2 is a functional marker expressed during immune activation [86], our results support the occurrence of testosterone-induced immunological activation of CD16 monocytes/DCs, and therefore, a neuroendocrine modulation of the immune response.…”
Section: Enhanced Immunological Response By Dendritic Cells In Male Hmentioning
confidence: 98%
“…Following our previous observation about an enhanced immunological response of circulating CD16+ monocytes/ dendritic cells (DCs) to antigen stimulation in male hypogonadism [84], we have recently analysed the effects of testosterone replacement therapy on the immunocellular response of these subjects [85]. Testosterone treatment induced overexpression of LAMP-2 on both classical (CD16-) and nonclassical (CD16+) monocytes/DCs, a very high correlation being observed between LAMP-2 expression on these cells and both the LH and FSH serum levels [85]. Of note, overexpression of LAMP-2 was detected both ex vivo and after immunogenic stimulation in vitro [85].…”
Section: Enhanced Immunological Response By Dendritic Cells In Male Hmentioning
confidence: 99%